Analyzing prognosis and comparing predictive scoring systems for mortality of COVID-19 patients with liver cirrhosis: a multicenter retrospective study - Shou-Yen Chen; Chip-Jin Ng; Yan-Bo Huang; Hsiang-Yun Lo (BMC Infectious Diseases)
Abstract Background Limited research suggested that liver cirrhosis is an independent risk factor for severe COVID-19, leading to higher hospitalization and mortality rates. This study aimed to identify the prognostic factors and validate scoring systems for predicting mortality in COVID-19 patients with liver cirrhosis. Methods This retrospective cohort study extracted electronic health records of patients with COVID-19 who visited the emergency department between April 2021 and September 2022. Adult COVID-19 patients with liver cirrhosis were included, excluding those aged < 18 years and who did not require hospitalization. The primary outcome was in-hospital mortality. The effectiveness of the scoring systems were analyzed for COVID-19 in-house mortality prediction. Results A total of 1,368 adult COVID-19 patients with liver cirrhosis were included in this study. Compared with the survival group, the non-survival group had lower vital signs such as systolic blood pressure and blood oxygen saturation, higher levels of white blood cells, creatinine, bilirubin, and C-reactive protein, and longer prothrombin time. Higher rates of intubation, oxygen use, and dexamethasone use were observed in the non-survivor group. The WHO ordinal scale, MELD, and MELD-Na scores showed good predictive ability for in-hospital mortality. Conclusions The WHO ordinal scale showed the best performance in predicting mortality in patients with cirrhosis and COVID-19. MELD and MELD-Na scores were also found good performance for mortality prediction. Coagulation function, intubation, and dexamethasone administration were the most significant prognostic factors.